Shelter Homes - Safe haven or prison? - Abdul Hamid, Haezreena Begum (Anti-Trafficking Review, 2023)
Shelters are the most common form of assistance available to trafficked persons in Malaysia and other countries. They may offer a safe and protected environment in which they can begin their recovery and access services such as legal, medical, or psychosocial aid. However, the rules imposed in the shelters and the overall victim protection mechanisms in Malaysia have been heavily criticised for violating human rights principles. This is because ‘rescued’ victims are forcibly detained in shelters until they are repatriated, which may take months or even a year. This article considers the conditions of victims’ detention from a socio-legal perspective. Drawing upon interviews with 29 trafficked women and 12 professionals from a shelter in Kuala Lumpur, it explores the women’s living conditions and access to legal support and mental and physical healthcare within the facility. The article concludes that routine detention of trafficked persons in shelters violates fundamental principles of international law and is therefore to be considered unlawful.